Análise da produção científica sobre competência informacional no contexto da ciência da informação no Brasil - Fabíola Maria Siqueira Rocha (2019)
The objective of this research is to analyze the scientific production on Information Literacy in the context of Information Science in Brazil, conveyed through articles indexed in SciELO, BRAPCI, theses and dissertations available in digital thesis and dissertation libraries or in the institutional repositories of the post- graduation programs in information science (PPGCI´s). The theoretical framework brings together ideas and authors from Information Science, Scientific Communication, Bibliometrics, Digital Libraries and Institutional Repositories and Information Literacy. This is a descriptive research with quantitative and qualitative approaches. The results show that in the period of 17 years, 68 theses and dissertations were identified in 10 post- graduation programs in information science. A total of 179 articles published in 37 scientific journals indexed in BRAPCI and SciELO, in the period 2000 to 2017. We identified 68 theses and dissertations in 10 graduate program in information science. The results show that the theme was more expressive in the PPGCI´s of the State University "Júlio de Mesquita Filho" (UNESP) with 17 publications, Universidade de Brasília (UnB) with 12 publications and Universidade Federal da Bahia (UFBA) with 10 publications. There is a great diversity of researchers who have only guided a work that shows a dispersion of productivity. Two professoras/researchers were identified as more productive advisors, sheltered in the PPGCI of UNESP. The subjects most frequently addressed in theses and dissertations are: competence in information with frequency six and informational competence with four replications. In BRAPCI, 34 scientific journals were found with a total of 158 articles. In Scielo only three scientific journals with 21 articles. Information Literacy a recent theme in Brazil and still does not have the cohesion and preferences of its researchers regarding the important problems to be studied in Brazil. In the literature studied, some researchers from other subjects took a tour of the theme and guided a dissertation or thesis or wrote an article only.